Developmental changes in metamotivation in children and adolescents (Journal of Imam Al-Kadhim College, 2023)
Abstract:The current research aims to find out the development of the level of meta-motivation among middle and high school students, according to the variables of age and gender, and to reveal the significance of the difference in the level of meta-motivation between the categories of each of the variables of age (11, 13, 15, 17) years and gender (male, female). . To achieve these goals, the researcher selected a sample consisting of (200) male and female students, with (50) students from the fourth grade of primary school who are (9) years old, and (50) students from the sixth grade students who are (12) years old, and ( 50 students from the third intermediate grade who are (15) years old, and (50) students from the fifth grade middle school who are (17) years old and of both sexes equally.
Keywords: development, beyond motivation, achievement, children, adolescents